Production Parameter Influence on Injection Gas Allocation in Gas Lift Wells Cluster - HERIYANTO (NIM 12204034), SYAHRUL
Continuous gas lift gas injection allocation optimization is very important to gain maximum oil rate. Gas injection allocation is influenced by many parameters such as water cut, productivity index, tubing size and length. Equal slope dQl/dQg method and equal slope dQo/dQg are used to find the optimum production rate for each well. These two methods are compared so the better one may be decided, which is the method that gives maximum oil production for the gas lift wells system. Several scenarios are created based on the values of water cut, productivity index, formation GLR, tubing size and length variation. The objectives are to find the influence of these parameters to injection gas allocation and to find the best method in determining gas injection allocation. Five models are developed with certain configuration and various production parameters. Injection gas amount is definite and it is less than the amount of gas that is needed for each well to get the optimum rate based on Gas Lift Performance Curve.